Financing of science as an important factor in the formation of knowledge-based economy (Journal of Economic Research & Business Administration, 2016)
This paper defines the role and justifies the importance of financing of science in the formation of knowledge-based economy. A statistical analysis of the financing of science in the Republic of Kazakhstan was carried out, on the basis of which features of the financing of science in Kazakhstan have been identified. Recommendations to encourage invest ment in science from the business and foreign sectors, particularly through the institution of a public-private partnership, were made.
Keywords: financing of science; SRED; knowledge-based economy; public-private partnership.